Analisis Modal Sosial dan Kemiskinan: Studi Cross Sectional 34 Provinsi di Indonesia - Mukharohmah, Maulia Siti; Wulandari, Meisyaroh Catur; Naufal, Hanif Afif (Ecoplan, 2024)
Research related to social capital and poverty is still rare in Indonesia. Thus, this research aims to analyze social capital by examining three dimensions: trust, social participation, and tolerance, as reflected in the social capital index, and their impact on poverty in Indonesia. This research involved secondary data from Statistics Indonesia in the book Social Capital Statistics, published in 2021. This research used three independent variables: the social capital index for trust, social participation, and tolerance. Meanwhile, the dependent variable was the percentage of poor people in each province in Indonesia. The data were analyzed using a multiple linear regression method with hypothesis testing, namely classical assumptions. The results showed that social capital, as described in the social capital index for trust and social participation, significantly influenced poverty reduction. Meanwhile, the social capital index for tolerance had a minimal effect. These findings suggest that government efforts should focus on increasing community participation to develop social capital as one of the efforts to deal with poverty alleviation in Indonesia.